Investigations on the parameters of multicomponent gas-metal plasma formed in the mixed molecular gases - Kovtun, Yu.V.; Syus'ko, E.V.; Skibenko, E.I.; Skibenko, A.I.; Shapoval, A.N; Yuferov, V.B. (Вопросы атомной науки и техники, 2017)
Studies have been made into the parameters of dense, multicomponent gas-metal plasma formed in the operating medium consisting of molecular gases such as nitrogen and oxygen, and also, the component metal Ti. Charge and elemental compositions of the generated plasma have been determined. Measurements were taken for the parametric and time dependences of the discharge current and the average density of plasma formed in the pulsed reflex discharge. Проведено исследование параметров плотной многокомпонентной газометаллической плазмы, образованной в среде рабочего вещества, состоящей из молекулярных газов, таких как азот и кислород, а также металлической компоненты Ti. Определены элементный и зарядовый составы образованной плазмы. Измерены параметрические и временные зависимости разрядного тока, средней плотности образованной плазмы в импульсном отражательном разряде. Проведено дослідження параметрів густої багатокомпонентної газометалевої плазми, утвореної в середовищі робочої речовини, що складається з молекулярних газів, таких як азот та кисень, а також металевої компоненти Ti. Визначено елементний і зарядовий склад утвореної плазми. Виміряні параметричні і часові залежності розрядного струму, середньої густини утвореної плазми в імпульсному відбивному розряді.